Compact Multiband Slot Antenna for WLAN/WiMAX Operations - Jianhui Bao; Qiulin Huang; Xinhuai Wang; Xiaowei Shi (International Journal of Antennas and Propagation)
A novel compact triple-band slot antenna is proposed for WLAN/WiMAX applications. With the use of three L-shaped slots and an open-ended slot on the ground plane, three resonant modes centered at 2.4/3.5/5.8 GHz are excited. These modes cover the standards of 3.5 GHz WiMAX and 2.4/5.8 GHz WLAN, three useful frequency bands for present wireless communication systems. The proposed antenna fed by L-shaped microstrip line has a small overall dimension of 16×30 mm2. The numerical and experimental results show that acceptable radiation characteristic is obtained over the operating bands.